EDUCATIONAL PROCESS PRIMARY CLASS STUDENTS CREATIVE ACTIVITY - Sharofutdinov Iqboljon Usmonjon o’g’li (Journals Park Publishing, 2022)
The development of the creative activity of primary school students was interpreted as a dynamic system consisting of many components.
Keywords: learning-cognitive activity, technology, creative activity, didactic-methodical, creative student, literacy.